If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = 4(w + -3) + -7w Reorder the terms: -24 = 4(-3 + w) + -7w -24 = (-3 * 4 + w * 4) + -7w -24 = (-12 + 4w) + -7w Combine like terms: 4w + -7w = -3w -24 = -12 + -3w Solving -24 = -12 + -3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3w' to each side of the equation. -24 + 3w = -12 + -3w + 3w Combine like terms: -3w + 3w = 0 -24 + 3w = -12 + 0 -24 + 3w = -12 Add '24' to each side of the equation. -24 + 24 + 3w = -12 + 24 Combine like terms: -24 + 24 = 0 0 + 3w = -12 + 24 3w = -12 + 24 Combine like terms: -12 + 24 = 12 3w = 12 Divide each side by '3'. w = 4 Simplifying w = 4
| x^2+5x+2.5=0 | | (x-8)*2=(3-x)*2 | | 0.3(x-2)=6 | | 3v^7-12v^5= | | -6*y-(-6)*1=6y | | k^4-5k^2+4= | | 9-3y-17=-11-5y+15 | | 10+15-10=15+10-5+5 | | 7x+3=4x+36 | | 10+15-10=15+10-10 | | 16-9+10=18+177-100 | | -1=2x | | 16-9+10=18+177-100+273 | | .5x^2+x=264 | | 0.6x^2=1.23+0.6 | | x^2-3=18-9x^2 | | -5t^8-20t^7-15t^6= | | x^2+27x+182=462 | | 5(3+3x)-4=26 | | (x-9)(x+7)=(x+4)*2 | | 1x+3=3x+4 | | 9-b^2= | | (x-9)(x+7)=(x+4)2 | | x=-2x^2-2x-1 | | 32=.5[(x+6)+(x+2)]x | | -(4x-7)=-(2x-1) | | a+5=-5a-5 | | 4x-3=x+14 | | x^2+1x-306=0 | | x^2+1x-3-6=0 | | 84=16x^2+10x | | x^2+2x-728=0 |